IIndentifikasi Jenis Ikan Pelagis Dan Pengelolaan Perikanan Tangkap Berkelanjutan Di Pangkalan Pendaratan Ikan Kasiwa Mamuju Provinsi Sulawesi Barat - Muhammad Ardiansyah; Danial Danial; Ardi Ardi (Universitas Mataram, 2024)
Fisheries are public resources (open access), or public resources, which can lead to overfishing or underfishing if not managed properly. This research aims to analyze fishing management at the Kaswa Mamuju Fish Landing Site (PPI) and focuses on aspects of sustainability, efficiency and safety of fishermen. This research involves collecting primary data through interviews and field observations as well as secondary data from related organizations. Based on the Kasiwa Mamuju Fish Landing Base survey, small pelagic fish are among the types of fish landed by PPI compared to other types of fish, the pelagic fish is tuna. The length of the fish taken varies depending on the species, and varies between 17 and 110 centimeters. In general, the fish landed at the Kasiwa Mamuju fish landing site are large and immature fish are not caught. The number of fishing boats is mostly motorboats and the number continues to increase every year until it reached 2,352 in 2017, 2,412 in 2018, and 2,575 in 2019. Therefore, the types of motorboats are increasing every year. The number of motorized vessels also increases every year, reaching 647 vessels in 2017, 650 vessels in 2018, and 897 vessels in 2019. There was a decrease in the number of non-motorized vessels in 2019, from 611 vessels in 2018 to 574 vessels.